Impactos operacionais da complementariedade de fontes de geração solar fotovoltaica e a biogás em sistemas de distribuição - Azevedo, Rodrigo Motta de (2016)
The current scenario of micro and mini distributed generation (micro and mini DG) in Brazil has been developing steadily and the power injection through the Distributed Generation (DG) regarding the development of small-scale sources of electricity production represents an alternative to the Brazilian energy grid. Considering the amended Normative Resolution No. 482/2012 (REN 482/2012) of the Brazilian National Agency of Electric Energy (ANEEL), which regulates the connection and the compensation of power systems in micro and mini DG through the REN 687/2015 expected for March 2016, it can be observed an incentive to the complementarity between the sources of DG and the integration of available resources. The insertion of micro and mini GD to the electrical distribution system presents numerous benefits. On the other hand, the penetration of these sources in an integrated manner will render this a complex system from operation and planning perspective, mainly related to operational characteristics of the network, such as voltage levels, active and reactive power loading, conductors loading, bidirectional power flow, electrical losses, among others. The aim of this study is to develop generation profiles of a photovoltaic solar system, producing a generic curve of hourly generation over a day. It is important for the power distribution companies to determine the degree of penetration at different times of a day so as to analyze operational impact on the feeders with the implementation of DG, since the companies regulate the number of Distributed Generations (DGs), but not the degree of penetration of the those at different times. Moreover, the complementarity will be carried out by overlapping the curves to integrate the ones from the photovoltaic systems with those from the biogas manure generation systems. The operational impact on the distribution network due to the insertion of these DG sources will be analysed. The aspects considered are voltage level, active and reactive power loading, conductors loading and electrical losses.